Kame or Moraine? A Sedimentological Study of a Glaciomarginal Landform at Niedźwiedziny (Great Polish Lowland) - Ewert-Krzemieniewska, Aleksandra (Geologos, 2014)
The succession is built of glaciofuvial deposits: a sandy/gravelly unit in the lower and middle parts, overlain by diamicton. Five lithofacies have been distinguished, which represent two facies associations: (1) a fuvial association evolving from a high-energy to a transitional to a shallow braided river on an alluvial fan, and (2) an association of cohesive deposits representing a glacigenic mass fow. The interpretation is based mainly on palaeocurrent data and differs from conclusions by earlier investigators. The ice-marginal zone is characterised by a large variety of glaciomarginal forms. Their sedimentology, morphology and palaeogeography are determined by successive phases of deglaciation. The results of the present study show that the character of the deglaciation in the study area changed with time from frontal to areal deglaciation.